Urban agriculture towards food security of Syrian refugees and vulnerable Lebanese host communities. Issue 5 (4th July 2019) - Dehnavi, Sudeh; Süß, Verena
ABSTRACT: Syrian refugees in Lebanon experience widespread food insecurity, implying lifelong negative effects on human development. Urban agriculture can improve food security status at the household level and incubate sustainable development. This article outlines lessons learnt from an urban agricultural project in Lebanon that aimed to provide food security for Syrian refugees and vulnerable host communities. The findings from a survey of 41 project participants show the potential to improve the project's performance in achieving its objectives by revising the project design. Fine-tuning project objectives based on available capacities and resources, beneficiaries' expectations, and integrating the social, cultural, technical and economic characteristics of the region into the project design could increase its success.